2017
DOI: 10.22159/ijpps.2017v9i11.21201
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Behavior of Carbamazepine Suspensions Using the Usp Dissolution Apparatus 2 and the Flow-Through Cell Method With Simulated Gi Fluids

Abstract: Objective: To characterize the dissolution behaviour of carbamazepine generic suspensions using the USP Dissolution Apparatus 2 and the flow-through cell method with simulated gastrointestinal fluids as dissolution media.Methods: Tegretol® suspension and two generic formulations were tested. Dissolution studies were performed using the USP Apparatus 2 (75 rpm and 900 ml of dissolution medium) and the flow-through cell method (laminar flow at 16 ml/min). Simulated gastric fluid (SGF) (with and without pepsin) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…On the other hand, USP apparatus IV was more beneficial in the development of a much more discriminating dissolution method than the pharmacopeial method, similar observations were stated by Medina et al [46] who studied in vitro dissolution profiles of carbamazepine IR generic tablet products using different dissolution apparatuses (II and IV). In a recent study, similar observation regarding USP apparatus IV and II was noticed for marketed suspensions of carbamazepine [47]. Again this was in accordance with the work done by Gite et al [51] on atorvastatin using USP apparatus I and IV.…”
Section: Beaker Methodssupporting
confidence: 87%
“…On the other hand, USP apparatus IV was more beneficial in the development of a much more discriminating dissolution method than the pharmacopeial method, similar observations were stated by Medina et al [46] who studied in vitro dissolution profiles of carbamazepine IR generic tablet products using different dissolution apparatuses (II and IV). In a recent study, similar observation regarding USP apparatus IV and II was noticed for marketed suspensions of carbamazepine [47]. Again this was in accordance with the work done by Gite et al [51] on atorvastatin using USP apparatus I and IV.…”
Section: Beaker Methodssupporting
confidence: 87%
“…Samples were previously filtered through a 0.45 µm membrane filter and the amount of DMAT was determined using a standard calibration curve. The absorbance of the samples was measured at 420 nm using UV/VIS [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of this comparative dissolution study for verapamil-HCl tablets agree with those reported by other authorsapparatus 4 was more accurate than USP Apparatus 2. Details of the successful association of MDT and modelparameters of naproxen tablets, ibuprofen suspensions, and fixed-dose combination formulations of acetaminophen and ibuprofen have been reported (27)(28)(29).…”
Section: ( )mentioning
confidence: 99%